PRODUKTIVITAS TERNAK KAMBING LOKAL DI KABUPATEN TOLITOLI - Usman, Usman (JSTT, 2016)
This research aims to find out characteristics and management of goat farming on small scale farming of Tolitoli Regency. It is also to find out factors influencing the goat productivity and development and to evaluate the goat population development and its reproduction performance. This is a qualitative research. The data was collected through survey and interview. The research was carried out within 2 months from February to March 2015. The area covers 3 districts, namely: (1) North Tolitoli, (2) North Dampal and (3) Dondo. The sample size was determined based on purposive sampling. Meanwhile, the data collection method was observation, interview and documentation. The data was identified and analyzed qualitatively by using percentage frequency table, then, they were interpreted descriptively. The research result from 3 districts reveals that goat productivity had not been done maximally, goats breeders are in productive age, their education qualification is on low level. However, they have experienced in breeding goats. Nevertheless, the business is part-time job. Whereas, the birth rate is as follow: 56 percent in North Tolitoli; 65.98 percent in North Dampal and Â 56 percent in Dondo.Â  Meanwhile, their mortality is as follow: 32.86 percent in North Tolitoli; 25.56 percent in North Dampal; and 37.50 percent in Dondo. The mortality rate of adult goats is as follow: 5.71 percent in North Tolitoli; 12.50 percent in North Dampal; and 5.36 percent in Dondo. It could be concluded that the goat farmers require training and advice from the relevant authoritiees to enhance their goat productivity and to improve their family income.